Numerical sedimentation particle-size analysis using the Discrete Element Method. (December 2015) - Bravo, R.; Pérez-Aparicio, J.L.; Gómez-Hernández, J.J.
Highlights: Sedimentation modeled with the Discrete Element Method and one-way coupling modelization. Discrete Element Method suited for millions of coupled contact particle interactions. Low Re numbers suitable for one-way coupling with drag of particle concentration. ASTM-D422, Buoyancy and Pipette sedimentation tests simulated and described. Simulation successful to improve interpretation and optimization of experiments. Abstract: Sedimentation tests are widely used to determine the particle size distribution of a granular sample. In this work, the Discrete Element Method interacts with the simulation of flow using the well known one-way-coupling method, a computationally affordable approach for the time-consuming numerical simulation of the hydrometer, buoyancy and pipette sedimentation tests. These tests are used in the laboratory to determine the particle-size distribution of fine-grained aggregates. Five samples with different particle-size distributions are modeled by about six million rigid spheres projected on two-dimensions, with diameters ranging from 2.5 × 10 − 6 m to 70 × 10 − 6 m, forming a water suspension in a sedimentation cylinder. DEM simulates the particle's movement considering laminar flow interactions of buoyant, drag and lubrication forces. The simulation provides the temporal/spatial distributions of densities and concentrations of the suspension. The numerical simulations cannot replace the laboratory tests since they need the final granulometry as initial data, but, as the results show, these simulations can identify the strong and weak points of each method and eventually recommend useful variations and draw conclusions on their validity, aspects very difficult to achieve in the laboratory.